The Toxicity and Antibacterial Effects of Povidone‐Iodine Irrigation in Fracture Surgery - Dong Wang; Xinli Huang; Wenrui Lv; Junlin Zhou (Orthopaedic Surgery, 2022)
Objective Surgical site infection is a common complication of surgery, especially in orthopedics. Povidone‐Iodine (PI) is one of the oldest and most commonly used disinfectants in surgery. However, the toxicity and antimicrobial effect of PI have not been discussed. In addition, no study has explored the optimum PI concentration for sterilization and tissue healing. This study explores the germicidal efficacy of different concentrations PI, in addition, the toxicity and antibacterial effects of PI irrigation in fracture surgery are also discussed. Methods Methicillin‐resistant Staphylococcus aureus and Pseudomonas aeruginosa (P. aeruginosa) were used to evaluate the germicidal efficacy of PI in vitro and in vivo. In vitro, the effects of PI on bacterial growth were analyzed. 2.5%, 1.25%, 0.5%, 0.25%, 0.05%, 0.025%, 0.005%, 0.0025% and 0% PI was added into the bacterial suspension, besides, the bacterial algebra and growth rate were tested. Meanwhile, the fluorescence intensity of viable bacteria was also tested to evaluate the effects of PI on bacterial survival. In vivo, first, femoral fracture with wound infection rat models were established. Second, thyroid gland sections, blood thyroxine, urinary iodine, wound local skin, muscle and bone tissue sections, serum creatinine and alanine aminotransferase, serum and bone local tissue interleukin‐6 (IL‐6), interleukin‐10 (IL‐10), bone morphogenetic protein (BMP‐2), vascular endothelial growth factor (VEGF) and transforming growth factor (TGF‐β1) were detected in rat femoral shaft fracture model with 5%, 2.5%, 0.5%, 0.05%, and 0% PI irrigation. Third, tissue bacteria culture was tested in rat femoral fracture with wound infection model with different concentrations PI irrigation. Results In vitro, 2.5%, 1.25%, 0.5% PI inhibited the growth of bacteria. 1.25%, 0.5% PI killed all the bacteria, while 0.25%, 0.05% PI had not killed bacteria after about 10 min. The iodine absorption of 5%, 2.5%, 0.5% PI irrigation did not cause thyroid injury. The 5%, 2.5%, 0.5% PI irrigation did not make serum creatinine and alanine aminotransferase abnormal and can remove bacteria from wounds. The 0.5%, 2.5% PI irrigation can promote tissue healing and increase BMP‐2, VEGF, TGF‐β1, IL‐10, in addition, decrease IL‐6. 5% PI irrigation would inhibit tissue healing, and increase IL‐6, decrease BMP‐2, VEGF, TGF‐β1, IL‐10. Conclusions Povidone‐Iodine was a widely used disinfectant and 2.5%, 1.25% and 0.5% PI could effectively kill bacteria. Five percent and lower concentration PI irrigation was safe and could not cause thyroid, kidney and liver damage. The 0.5% PI irrigation was beneficial for tissue healing but 5% PI irrigation was the opposite.